THE STRATEGIC ROLE OF ORGANIZATIONAL LEARNING IN LINKING INTERNAL CAPABILITIES AND FIRM PERFORMANCE AMONG INDONESIAN SMES - Ahmad Reza Hariyadi; Rawiyah Abd Hamid; Nur Yuhainis Ab Wahab (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Small and Medium Enterprises (SMEs) play a strategic role in Indonesia’s economic development, yet many face persistent challenges in transforming internal resources into sustainable firm performance. This study aims to examine the strategic role of organizational learning in linking internal capabilities and firm performance among Indonesian SMEs. Using a qualitative research design, this study adopts a library research approach combined with content analysis to synthesize recent scholarly literature on organizational learning, internal capabilities, and SME performance. The analysis focuses on key dimensions of internal capabilities, including managerial competence, innovation capability, operational flexibility, and knowledge management, and how these capabilities are strengthened through organizational learning processes such as knowledge acquisition, knowledge sharing, experimentation, and continuous improvement. The findings indicate that organizational learning plays a mediating and strategic role in transforming internal capabilities into improved firm performance. SMEs that foster a strong learning culture demonstrate higher levels of innovation, adaptability, and productivity in dynamic business environments. The study contributes to the strategic management and SME literature by highlighting organizational learning as a critical mechanism for enhancing resource utilization and long-term competitiveness. Practically, the findings provide insights for SME managers and policymakers to design capacity-building programs and knowledge-based development strategies that support sustainable SME growth in emerging economies